BANGAN MEDIA PEMBELAJARAN KARTU UNO PADA TEMA 7 SUBTEMA 1 DI KELAS V SD - Anggi Umayrah; Eva Betty Simanjuntak (Universitas Negeri Medan, 2023)
Abstract: The purpose of this research is to determine whether the Uno Card Learning Media in Theme 7 Sub-theme 1 in Class V of Pelangi Medan Private Elementary School is feasible, practical, and effective for use in learning. This type of research is development research using the ADDIE development model. The subjects of this study consisted of material experts, learning media experts and 14 grade V students of Pelangi Private Elementary School, Medan City. The objects in this study are learning media, the scale of student responses to learning media and student learning outcomes. The results showed that the feasibility test was (1) the expert test of learning materials was in the very good classification (85.45%), (2) the learning media expert test was in the very good classification (91%), then the practicality test was in the classification very practical (91.5%). UNO Card Media Effectiveness at stage pretest student scores with an average of 55.64% in the low effectiveness category, and at stage posttest student scores increased after using the UNO Card learning media with an average of 88.5% in the